Population Fluctuation and the Adoption of Food Production in Prehistoric Korea: Using Radiocarbon Dates as a Proxy for Population Change. Issue 6 (16th November 2017) - Oh, Yongje; Conte, Matthew; Kang, Seungho; Kim, Jangsuk; Hwang, Jaehoon
Abstract: Population growth has been evoked both as a causal factor and consequence of the transition to agriculture. The use of radiocarbon ( 14 C) dates as proxies for population allows for reevaluations of population as a variable in the transition to agriculture. In Korea, numerous rescue excavations during recent decades have offered a wealth of 14 C data for this application. A summed probability distribution (SPD) of 14 C dates is investigated to reconstruct population trends preceding and following adoptions of food production in prehistoric Korea. Important cultivars were introduced to Korea in two episodes: millets during the Chulmun Period (ca. 6000–1500 BCE) and rice during the Mumun Period (ca. 1500–300 BCE). The SPD suggests that while millet production had little impact on Chulmun populations, a prominent surge in population appears to have followed the introduction of rice. The case in prehistoric Korea demonstrates that the adoption of food production does not lead inevitably towards sustained population growth. Furthermore, the data suggest that the transition towards intensive agriculture need not occur under conditions of population pressure resulting from population growth. Rather, intensive rice farming in prehistoric Korea began during a period of population stagnation.